The mechanism of dynamic development of the scientific and innovative potential of teaching staff in the context of participatory management - Абдигапбарова , Улжаркын; Тапалова, Ольга; Жиенбаева , Надежда (Pedagogy and Psychology, 2023)
The development of the scientific and innovative potential of the teaching staff directly depends on the effectiveness of managerial decisions, which is best met by participatory management, as it creates equal relationships between the participants in this process, giving them the opportunity to regulate the quality of the implemented technologies of scientific and innovative activity, pedagogical scientific intuition and improvisation of pedagogical skills. The mechanism of participatory management developed by us will allow: to determine the driving forces for the development of the scientific and innovative potential of a university teacher; create a "comfortable" environment for the effective implementation of the process of developing the teacher's scientific and innovative potential; to optimize the pedagogical strategy of the "ascent" of the teacher to the optimal level of development of scientific and innovative potential for him. The creation of a mechanism for participatory management of the development of the scientific and innovative potential of a university teacher ensures an effective transfer of pedagogical technologies. The study was conducted within the framework of the project of the Ministry of Education and Science of the Republic of Kazakhstan IRN AR14872123 "Participatory management of the development of scientific and innovative potential of the faculty of a research university."